Managers as Knowledge Carriers - Explaining Firms' Internationalization Success with Manager Mobility - Philipp Meinen; Pierpaolo Parrotta; Davide Sala; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2018)
How does “what managers know” affect firm performance on international markets? This question is of considerable importance in the international economic literature. Answering it will be key for comprehending the way firms' varying performance on international markets is shaped by the human factor. This paper proposes managerial mobility as an integral part of such an answer. Catering products to an international customer base entails a learning process, which, to a large degree, stems from the experience of doing it. Therefore, different employers immensely contend for managers' highly valuable export experience. As managers can accept better and better positions from several offers, they may become highly mobile, thus having a notable impact on possibly multiple firms' internationalization. Exploiting a rich panel data set, the paper thoroughly tests this idea by discriminating between knowledge ascribable to managers' former job experience and that attributable to their personal background. The paper uses a novel identification strategy grounded in on-the-job search theory to correct estimates for the presence of self-selected mobility flows. A core finding of the paper is that the maximum return to expertise acquisition is realized for those managers with previous experience in commercializing differentiated products in specific markets.
Keywords: F14; F16; F23; M12; 330; management; mobility; experience; export